Dismantle Rules of Lighting In Dance Creation - Herlinda Mansyur (Universitas Negeri Medan, 2022)
This research aims to provide a new discourse to the younger generation about the world of creating dance works. The field of development dance work creation has resulted in new discoveries ranging from creation methodologies to movement techniques that require dancers to improve fast. A choreographer must investigate every dance element that has been